ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA TINGKAT SEKOLAH DASAR DI KOTAMADYA YOGYAKARTA - Trisniawati Trisniawati (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2017)
This study aims to describe the attainment of mathematical problem solving ability among elementary school students in Yogyakarta Municipality and to describe errors that they make in answering the items in the test of mathematical problem solving ability. This was a qualitative and case study research. The research population comprised all elementary school students in Yogyakarta Municipality. Then, 3 elementary schools in Yogyakarta Municipality were randomly selected based on upper, middle, and lower ranks, namely SD Negeri Ungaran Yogyakarta, SD Bina Anak Sholeh Yogyakarta, and SD Negeri Karanganyar Yogyakarta. The study was carried out in Grade V in November 2015. The research instruments were a test of mathematical problem solving ability and an interview guide. Based on the data from the test of mathematical problem solving ability, interviews were conducted by involving 5 students from each elementary school. The results of the study show that the mathematical problem solving ability among elementary school students in Yogyakarta Municipality is still low, namely less than 68. Their mathematical problem solving ability at the stage of understanding a problem is 52.37%, at the stage of planning to solve a problem it is 29.091%, at the stage of solving a problem it is 23.09%, and at finding out an alternative it is 8.88%. The results indicate that many students have not attained the stage of rechecking by finding out an alternative way (solution). The errors that the students often make include inaccurate data, inaccurate procedures, unavailable conclusions, skill hierarchy problems, and indirect manipulations